Raider of the lost N-glycans – Localizing rare and frequently overlooked IgG N-glycans with sulfation or bisecting LacNAc - Burock, Robert; Chuzel, Léa; Kähne, Thilo; Reichl, Udo; Rapp, Erdmann; Hennig, René (Frontiers in Molecular Biosciences, 2025)
Immunoglobulin G (IgG) is the most abundant immunoglobulin in human blood. Here it plays a central role in the immune system by recognizing antigens and mediating effector functions of the humoral immune defense. The role of IgG N-glycosylation in many of these processes is well known. However, low-abundant N-glycans with special features, like sulfation or galactosylated bisecting N-acetylglucosamine (GlcNAc), are rarely accounted for due to their challenging detection. These structures are frequently overlooked and their presence on IgG is disputed mainly because specialized enrichment and analysis strategies are required for their detection. Consequently, they are disregarded in studies of IgG N-glycosylation, which in general is well understood. But functional knowledge is mainly based on N-glycans found in IgGs Fc region that contains a conserved N-glycosylation site. In contrast, the influence of N-glycosylation within the Fab region is less well understood, partly because it is present at non-conserved glycosylation sites found on only 10%–25% of IgG. Here, we performed an in-depth analysis of released N-glycans derived from intact IgG, its Fab and its Fc regions. For this we combined proteolytic fragmentation of IgG obtained by affinity chromatography and exoglycosidase sequencing based on multiplexed capillary gel electrophoresis with laser-induced fluorescence detection (xCGE-LIF). By using these simple and readily available methods, we localized N-glycans bearing sulfation or galactosylated bisecting GlcNAc on IgG, and found them on IgA, too. Further, we proved sulfation of N-glycans using an apo-sulfatase in an epitope-directed glycan enrichment (EDGE-) profiling workflow. With our novel findings, we provide insights into hypothetical biological implications of these low-abundant N-glycan features and advocate for their inclusion in future studies of IgG N-glycosylation.